Air Pollution XX 2012
DOI: 10.2495/air120221
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of air quality dispersion models at urban intersection of an Indian city: a case study of Delhi city

Abstract: Air quality modelling plays an important role in formulating air pollution control and management strategies by providing guidelines for better and more efficient air quality planning. Several air quality dispersion models are used to evaluate the urban air quality. The performance and efficiency of an air quality model are mainly depends upon the accurately interpretations of the complex interactions between various atmospheric, emission and topographic parameters involved in the air pollution problem. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Vehicles in major metropolitan cities of India are estimated to account for 70% of CO, 50% of HC's, 30-40% of NOx, 30% of SPM and 10% of SO 2 of total load of these cities, of which 2/3 rd is contributed by 2wheelers alone. This rapid growth of motor vehicles ownership and activities in Indian cities are causing a wide range of serious health, environmental and socio-economic impacts (Khare et al, 2012). Air pollutants, both gaseous and particulate, are known to produce a measurable effect on plants.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicles in major metropolitan cities of India are estimated to account for 70% of CO, 50% of HC's, 30-40% of NOx, 30% of SPM and 10% of SO 2 of total load of these cities, of which 2/3 rd is contributed by 2wheelers alone. This rapid growth of motor vehicles ownership and activities in Indian cities are causing a wide range of serious health, environmental and socio-economic impacts (Khare et al, 2012). Air pollutants, both gaseous and particulate, are known to produce a measurable effect on plants.…”
Section: Introductionmentioning
confidence: 99%
“…AERMOD [13] and ADMS-Urban [14], are highly advanced and complex but user-friendly. They are performing satisfactorily with old generation line source dispersion models such as CALINE 4, GFLSM and DFLSM [15]. Kumar et al, [16] observed that AERMOD has a tendency to under-predict both under stable and unstable conditions when the model was applied for Ohio, USA.…”
Section: Introductionmentioning
confidence: 91%
“…Gases and particles get emitted in the atmosphere from natural and anthropogenic activities viz. residential cooking, vehicles, industries, construction, and deforestation [4][5][6][7]. About half of the urban population being monitored is exposed to air pollution that is at least 2.5 times higher than the levels with WHO air quality guidelines.…”
Section: Introductionmentioning
confidence: 99%